PERANAN PERUBAHAN SOSIAL TERHADAP MACAM ALAT BUKTI DALAM RUU KUHAP - TRI WAHYU WIDIASTUTI (Wacana Hukum, 2009)
Abstract: Law and societies are similarly dynamic and change through time. The changes and development of societies change law as well s that law is still useful to society. The development of science and technology influence the people behavior and the crimes as well, the quantity and the quality. Therefore, law must accommodate the changes t overcome the changing crimes. A god law gives justice and purpose to the society Keywords: social changes, evidence.